From Borderline to Borderland. Old Devices in New Narratives - Vallorani, Nicoletta (Margins/Marges/Margini, 2024)
I want to reflect on margins and marginality focusing on the ways in which, approximately from the 1990s onward (Bennett et al. 2005, 4), the very notion of border has been changing over time. What used to be a line to be crossed to reach safety or freedom or a kind of protection, has gradually widened and become an extended area whose nature challenges the traditional organization of maps in which discrete sovereign territories are by lines and marked by different colors. I am focusing on this specific transformation, that in fact produces a strong impact on the migration journey and articulates the space/time in between the departure from one’s own motherland and his/her final destination – often a mirage rather than a real possibility. Borders increasingly appear as complex composites not only when they are extended in space – as happens in the case of Mediterranean crossings – but also when they expand in the “time of waiting” spent in refugee camps or other carcereal locations. I am considering recent artistic representations and forms of artivism, all of them focusing on the Mediterranean area as to see how new maps of the margins are drawn. Chris Cleave (2008), Morgan Knibbe (2015), Mario Badagliacca (2016-ongoing), Valeria Luiselli (2017), as well as the artists working at the Trojan Women Project seem to pursue the idea that to renew their gaze on the enormous tragedy of migration, we need new tools, more dynamic strategies to see how, following the progress of globalization, borders change their nature, and the migrant journey to cross them much more complex.